Effect of sintering temperature and thermoelectric power studies of the system MgFe2-xCrxO4 - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Gavali, L. V.; Sasikala, R.; Mulla, Imtiaz S. (Solid State Sciences, 2009)
Mixed metal oxides showing the spinel structure exhibit interesting structural and electrical properties. Substances with specific compositions in the system MgFe2-xCrxO4 were synthesized by the simple co-precipitation method and have been investigated by X-ray diffraction (XRD) and scanning electron microscope (SEM) to study the effect of temperature on the size of particles and grains. The infrared spectrum shows, two strong bands around 600 and 500 cm(-1). An elemental composition of one of the samples, MgFeCrO4 was found by energy dispersive X-ray spectroscopy (EDS). The thermoelectric power measurements carried out from room temperature to 500 degrees C, show both n-type and p-type behavior. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: synthesis; Temperature effect; Thermoelectric studies

Synthesis and characterization of cobalt substituted zinc ferri-chromites prepared by sol-gel auto-combustion method - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Patil, R. P.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Mixed metal oxides having spinel structure shows interesting structural properties. In the present investigation, cobalt substituted zinc ferri-chromites were prepared by sol-gel auto-combustion method. The completion of solid state reaction and the formation of spinel phase were identified using X-ray diffraction technique. All the compounds exhibit cubic spinel symmetry and lattice constant shows an irregular trend with substitution of Co. Infra-red spectral studies shows an two strong bands, one around 600 cm(-1) which is attributed to the intrinsic vibrations of tetrahedral complexes and the other at 400 cm(-1) is due to octahedral one. The morphology and size of the particles was found out by scanning electron microscopy while the elemental compositions by elemental dispersive X-ray spectroscopy. The various compounds of the present system Zn1-xCoxFeCrO4 were also investigated for their thermal and electronic studies.